Optimizing Human Resource Management in Education through Big Data and Learning Analytics - Hermania Bhoki (JTP - Jurnal Teknologi Pendidikan, 2025)
This study explores the optimization of Human Resource Management (HRM) in education through the integration of Big Data and Learning Analytics. Despite the growing availability of educational data, many institutions still face challenges in fully utilizing these technologies to enhance HRM practices. The research focuses on how Big Data and Learning Analytics can improve key HRM processes such as recruitment, performance evaluation, professional development, and teacher retention. By reviewing existing literature, this study identifies gaps in the current use of these technologies and proposes strategies to overcome barriers related to their implementation. The findings suggest that integrating Big Data and Learning Analytics into HRM practices can significantly improve decision-making, foster teacher development, and ultimately contribute to better academic and non-academic outcomes. The study concludes that a data-driven approach to HRM is essential for optimizing educational management and achieving sustainable improvements in teaching and learning. Further research is needed to explore effective strategies for the integration of these technologies into HRM practices to fully realize their potential in education.